1995
DOI: 10.1159/000244259
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Osteocalcin in Normal Pregnancies and Pregnancies Complicated by Fetal Growth Retardation or Diabetes mellitus

Abstract: A homologous radioimmunoassay for human osteocalcin was used to measure cord serum osteocalcm concentrations in normal pregnancies and in pregnancies complicated by intrauterine growth retardation (IUGR) and diabetes. The mean osteocalcin concentrations in term newborns (100–110 μg/l) were comparable with levels that we previously measured in pubertal children. There was a small increase in mean osteocalcin concentrations during the third trimester of fetal life, with the maximum at 35 weeks; between weeks 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…IUGR fetuses also show evidence of disturbed endocrine regulation of bone formation. Serum levels of active vitamin D and osteocalcin are significantly decreased and may be responsible for decreased bone mineralisation as well as decreased bone growth 70,71 …”
Section: Fetal Endocrine Responsesmentioning
confidence: 99%
“…IUGR fetuses also show evidence of disturbed endocrine regulation of bone formation. Serum levels of active vitamin D and osteocalcin are significantly decreased and may be responsible for decreased bone mineralisation as well as decreased bone growth 70,71 …”
Section: Fetal Endocrine Responsesmentioning
confidence: 99%
“…18 It has been suggested that the hypocalcaemia in the offspring of diabetic rats are due to a defective bone maturation in the fetus itself as a result, fetus minimizes its Ca 2+ requirements. 35 Earlier Potu et al have shown that PECQ can increase the mesenchymal stem cell proliferation and subsequently their differentiation into osteoblasts. 36 In an in vitro study, the Gopalakrishnan et al have demonstrated the positive effect of synthetic estrogen on bone mineralization process in hyperglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with T1D serum osteocalcin levels have been shown to be lower in patients with complications (retinopathy and/or proteurinuria) than in patients with diabetes without complications [31,33]. In newborns to mothers with diabetes, umbilical cord osteocalcin levels have been shown to be decreased [34].…”
Section: Osteocalcin Diabetes and Bonementioning
confidence: 99%